Computational structural analysis and modeling of plant PRR DORN1 ectodomain - Siddiqui, Aorchie (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.